2009
DOI: 10.1002/ange.200905413
|View full text |Cite
|
Sign up to set email alerts
|

High‐Index Faceted Platinum Nanocrystals Supported on Carbon Black as Highly Efficient Catalysts for Ethanol Electrooxidation

Abstract: Facettenreich: Platin‐Nanokristalle auf Industrieruß wurden elektrochemisch synthetisiert (HIF‐Pt/C, siehe Bild). Die Nanokristalle sind durch hoch indizierte Facetten und eine hohe Dichte an atomaren Stufen gekennzeichnet. Dies macht sie bei der Elektrooxidation von Ethanol mindestens zweimal so aktiv und CO2‐selektiv wie käufliche Pt/C‐Katalysatoren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 18 publications
2
58
0
1
Order By: Relevance
“…[257] This problem was overcome by Sun, Wang, and co-workers, who have developed an electrochemical method to prepare NPs terminated by high-index facets. [94,[258][259][260][261][262][263] NPs of other preferential shapes, such as concave hexoctahedral (enclosed by {hkl} facets), [264] trapezohedral ({hkk} facets), [263,264] and nanorods (various {hk0} or {hkk} facets) [264,265] as well as metals (Pt, [94,264,266] Pd, [261,264,265] Fe, [267] PdPt, [260] and PtRh), [263] have similarly been produced by adjusting the synthetic conditions. 750 nm) were electrodeposited on a glassy carbon electrode.…”
Section: Electrochemistry At Preferentially Shaped Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…[257] This problem was overcome by Sun, Wang, and co-workers, who have developed an electrochemical method to prepare NPs terminated by high-index facets. [94,[258][259][260][261][262][263] NPs of other preferential shapes, such as concave hexoctahedral (enclosed by {hkl} facets), [264] trapezohedral ({hkk} facets), [263,264] and nanorods (various {hk0} or {hkk} facets) [264,265] as well as metals (Pt, [94,264,266] Pd, [261,264,265] Fe, [267] PdPt, [260] and PtRh), [263] have similarly been produced by adjusting the synthetic conditions. 750 nm) were electrodeposited on a glassy carbon electrode.…”
Section: Electrochemistry At Preferentially Shaped Nanoparticlesmentioning
confidence: 99%
“…A further enhancement in specific activity has been demonstrated by modifying the high-index facets of preferentially shaped NPs with a second metal beneficial for a specific reaction, such as Pd for formic acid oxidation [260] or Rh for ethanol oxidation. [259] Furthermore, smaller NPs of this type are relatively unstable due to lower stabilization from the bulk material, and adsorption and reaction of species during electrocatalysis may cause small NPs to change their shape and lose the enhanced activity. [270] Although the use of tailored, preferentially shaped NPs (either enclosed by basal planes or by high index facets) is a seemingly straightforward approach to boost the catalytic activity for some reactions, such NPs are quite large (typically > 10 nm for basal plane faceted NPs and 20-150 nm for highindex NPs) compared to commercial catalysts (2-4 nm).…”
Section: Electrochemistry At Preferentially Shaped Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concave Pd polyhedra exhibit the lowest ECSA among the four catalysts, which may be caused by their large particle size. According to the above results, it can be safely concluded that the observed high electrocatalytic activities of the concave Pd polyhedra could be attributed to the presence of the large number of atomic steps [35] and/or surface relaxation. The peak current density of ethanol oxidation in the positive potential scan was 1.41, 0.36, 0.21, and 0.61 mA cm À2 on the concave Pd polyhedra, truncated Pd octahedra, Pd black, and Pd/C, respectively (Figure 3 a).…”
mentioning
confidence: 72%
“…[3] This discovery is receiving increasing attention from public and private institutions interested in the setup of fossil fuel-free and environmentally friendly processes. For example, although a variety of metal (e.g., Pt, Pd, and Au) NPs with HIFs have been synthesized through electrochemical square wave potential deposition (SWPD) or wet chemistry methods, [8][9][10][11][12][13][14] the particle sizes are usually much larger than those of practical catalysts (2-10 nm). [7] The exploitation of the catalytic properties of the HIFs depends on the availability of methods capable of generating supported NPs with high-index terminations as well as controlling the particle size and metal loading.…”
mentioning
confidence: 99%